Current assessment results of the efficacy and safety of scleroplasty in progressive myopia - E. N. Iomdina; E. P. Tarutta; G. A. Markosian; J. I. Gavrilova (Российский офтальмологический журнал, 2021)
The purpose of the review is to analyze the data of recent studies (performed in the last two decades) of the efficacy and safety of sclera reinforcement surgeries for progressive myopia in children and adults. Short-term and long-term observation results are presented, indicating the impact of the initial degree of myopia, the patient's age, surgical technique and the choice of plastic material on the outcome of the intervention and the further course of the myopic process. The advantages of a biologically active synthetic graft are described, which makes it possible to deposit drugs that stimulate scleral crosslinking and have a biomechanical, trophic and hemodynamic effect. Crosslinking of scleral collagen is a promising approach to the treatment of myopia.